The population dynamics of three polyphagous owlet moths (Lepidoptera: Noctuidae) and the influence of meteorological factors and ENSO on them - Medrano, Magaly Fonseca (2019)
The owlet moths (Lepidoptera: Noctuidae) Anicla infecta (Ochsenheimer 1816), Elaphria agrotina (Guenée 1852) and Spodoptera frugiperda (J.E. Smith 1797) occur in the entire American continent. These polyphagous moths have a preference for grasses, and have different biological habits. In this study, the populations of these three species were evaluated monthly with light traps in the Brazilian Savannah, ranging a span of four crop seasons (from July, 2013 to June, 2017). The population data were analyzed and correlated with the meteorological variables: maximum temperature, minimum temperature, relative humidity and precipitation. A total of 4719 individuals were collected in the following percentages: A. infecta (n = 459; 9.73%), E. agrotina (n = 1809; 38.33%) and S. frugiperda (n = 2451; (51.94%). The abundance of all species went down from the first crop season (2013/2014) to the third (2015/2016). In the fourth crop season (2016/2017), the populations of A. infecta and E. agrotina stabilized, but the abundance of S. frugiperda experienced further decrease. The numbers of individuals of three species declined when precipitation was much above (crop season 2014/2015) and below (crop season 2015/2016) than expected by the climatological normal. There were significant, but different degrees of correlation, between the meteorological factors and the ONI index (Oceanic Niño Index - indicator for monitoring El Niño-Southern Oscillation or “ENSO”) with respect to monthly population variations. The results are discussed in accordance with principles of the Integrated Pest Management (IPM) in mind, given the continental distribution and agricultural importance of the three owlet moth species studied.